Belgium : 2005 Article IV Consultation Staff Report; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2006)
This 2005 Article IV Consultation highlights that Belgium's growth has picked up following weakness in early 2005, mainly reflecting a negative contribution from the external sector and weak household consumption owing to high energy prices. The authorities and the IMF staff project GDP growth to strengthen into 2006 to somewhat more than 2 percent, as demand from trading partners increases further. Private consumption is projected to pick up in response to tax cuts, and residential construction is likely to remain resilient, even though housing price growth is likely to slow.